2015
DOI: 10.12968/bjon.2015.24.sup10.s22
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and early detection of cervical cancer in the UK

Abstract: This literature review explores the prevention and early detection of cervical cancer in the UK. Current findings indicate that there is a risk for women under the age of 25 years, who may develop cervical cancer. There appears to be a gap in UK policy that may overlook these women, who are beneath the age for initial screening but exceed the age for vaccination. Despite the inextricable link between sexual activity and cervical cancer, cervical screening and sexual health promotion still appear to be disjoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 3 Although widespread implementation of screening programs has decreased the incidence and mortality of this disease, clinical outcomes in CC patients vary distinctly and are very challenging to predict accurately. 4 , 5 The long-term survival of CC is closely related to the clinical stage of neoplasm at diagnosis. 6 Therefore, more sensitive biomarkers for early diagnosis and more efficient and safer treatments are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Although widespread implementation of screening programs has decreased the incidence and mortality of this disease, clinical outcomes in CC patients vary distinctly and are very challenging to predict accurately. 4 , 5 The long-term survival of CC is closely related to the clinical stage of neoplasm at diagnosis. 6 Therefore, more sensitive biomarkers for early diagnosis and more efficient and safer treatments are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is believed that the two viral infections are linked to 5% of all cases of cervical cancer [ 10 ]. Regular follow-up through Pap smear-based testing, detection and typing of HPV, and using HPV vaccination has remarkably reduced cervical cancer incidence worldwide [ 11 ]. Also, high-risk HPV is an important biomarker of prognosis in cervical cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Etiological studies have shown that cervical cancer is closely associated with human papillomavirus (HPV) infection, but most cases of HPV infection are self-limiting, and only a small proportion of HPV-infected individuals eventually develop cervical cancer ( Foran and Brennan, 2015 ). Differences in host tumor susceptibility can lead to different outcomes of HPV infection ( Forouzanfar et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%